Interfacing of sensors to a single board computer - Koshy, Jefferson Jed (2019)
Smart systems have become more and more a part of modern society as technology becomes more advanced and have come to homes, workplaces, and schools. As such the need for making affordable, customizable and low-powered systems have become the goal of many developments. In this project, a smart home automation system was developed using the GraspIO Cloudio board mounted on a Raspberry PI B+ and an Xbee Transmitter on an Arduino Board. The project’s goal was to make a smart home automation system with microcontrollers that would be able to collect data from sensors and transmit the data over two emerging technologies, the Internet-Of-Things and a mesh network called Zigbee. The system was to be low-powered and have capabilities such as measuring humidity, temperature, and rain, as well as have other functions like offsite phone monitoring, voice activated responses, and autonomous home monitoring mode.